Forty Years After the Islamic Revolution of Iran: An Indonesian Perspective - Sofjan, Dicky (Program Studi Studi Agama-Agama, Fakultas Ushuluddin dan Filsafat, Universitas Islam Negeri (UIN) Sunan Ampel Surabaya, 2019)
Following 40 years of Khomeini’s Islamic Revolution in Iran, how does Indonesia view Iran then and now? Is the exportation of the Revolution now relevant amid the contemporary political constellation in the Middle East and the world? Does Shia Islam remain to pose a sociopolitical problem today in the largest Muslim nation? In view of the current political standoff with the United States of America, will the system, based on Velayat-e Fagheh (Guardianship of the Jurist), remain strong against all odds? This article explores these questions based on personal reflections, experiential learning and continuous engagement in and with Iran. [Setelah 40 tahun Revolusi Islam pimpinan Khomeini berhasil memukau dunia, menarik untuk melihat pandangan Indonesia terhadap Iran, yang dulu dan sekarang. Apakah semangat revolusi masih relevan terkait dengan konstelasi politik Timur Tengah dan dunia kontemporer? Apakah persoalan Syiah masih dipandang sebagai pemicu berbagai problema sosio-politik di Indonesia? Melihat permusuhan Amerika terhadap Iran, apakah sistem Velayat-e Fagheh (Kepemimpinan oleh Faqih) masih relevan menghadapi berbagai tantangan yang dihadapi Iran saat ini? Artikel ini berupaya mengeksplorasi pertanyaan-pertanyaan di atas berdasar refleksi dan pengalaman personal serta pengamatan terhadap situasi perkembangan di Republik Islam Iran.]